2020
DOI: 10.2196/17247
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Modeling of Discussions Related to Gastrointestinal Discomfort in French-Speaking Online Forums: Results of a 15-Year Retrospective Infodemiology Study

Abstract: Background Gastrointestinal (GI) discomfort is prevalent and known to be associated with impaired quality of life. Real-world information on factors of GI discomfort and solutions used by people is, however, limited. Social media, including online forums, have been considered a new source of information to examine the health of populations in real-life settings. Objective The aims of this retrospective infodemiology study are to identify discussion topi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Additionally, topic modeling and RNNs are commonly used for clinical/biomedical Web text mining. Schäfer et al [ 60 ] identified “Web-based discussion topics associated with Gastrointestinal discomfort and its perceived factors in Web-based messages posted by users of French social media (p. 1)” using topic modeling to provide real-world evidence for caregivers. Chen et al [ 61 ] employed topic modeling and visual analytics techniques to characterize textual content generated during Internet behavioral health interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, topic modeling and RNNs are commonly used for clinical/biomedical Web text mining. Schäfer et al [ 60 ] identified “Web-based discussion topics associated with Gastrointestinal discomfort and its perceived factors in Web-based messages posted by users of French social media (p. 1)” using topic modeling to provide real-world evidence for caregivers. Chen et al [ 61 ] employed topic modeling and visual analytics techniques to characterize textual content generated during Internet behavioral health interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Health information is already shared by many web users on web forums and digital platforms ( 35 , 36 ). The processing of online natural language has been identified as an opportunity to enable sentiment analysis ( 37 ) or assess quality of life ( 38 ) which can be used as a complement to conventional methods of heath information tracking ( 39 ) by considering environmental, psychological and lifestyle factors ( 40 , 41 ). Interestingly, even more participants confirmed that they would agree to interact with a chatbot during the conduct of clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that adult patients tend to focus on gastrointestinal discomfort in their posts, and the top three causes were psychological factors, food, and allergens [ 27 ]. Using the LDA algorithm and an LDA visualization tool, we identified and visualized 6 main topics in our study from 2 health forums, one for discussion among the parents who cared for teen patients with IBS and another for discussion among the adolescent patients themselves.…”
Section: Discussionmentioning
confidence: 99%